Where platforms meet infrastructures: digital platforms, urban resistance and the ambivalence of the city in the Italian case of Bologna. (1st January 2020) - Marrone, Marco; Peterlongo, Gianmarco
Abstract : This article focuses on the central and ambivalent role that cities play in the context of platform capitalism. While on the one hand, urban spaces have become an advanced ground for the operations of capital, on the other they have also become the main stage for resistance movements. The city is thus emerging as a decisive political and socio-economic dimension for understanding the impact of digital platforms on workers and on society. By presenting two Italian case studies from the city of Bologna, we aim to shed light on how cities not only provide the necessary resources and infrastructures for platforms to rise and operate, but also give rise to movements to organise and resist these developments.